The Implementation of a Multisensory Approach on Overcoming Vocabulary Learning Difficulties Among Dyslexic Junior High School Students - Ariqqah Raihana; Maryati Salmiah (Universitas Islam Negeri Palopo, 2026)
This study explores the implementation of a multisensory approach in teaching vocabulary to dyslexic students in an inclusive junior high school English classroom in Indonesia. The research employed a qualitative case study involving one English teacher selected through purposive sampling. Data were collected through semi-structured interviews, document analysis of lesson plans, and non-participant classroom observations. The data were analyzed using thematic analysis with methodological triangulation to ensure credibility. The findings revealed that multisensory elements were present in classroom practice, particularly through visual and auditory activities such as PowerPoint presentations, pronunciation modeling, and repetition exercises. However, kinesthetic and tactile components were limited and were not systematically integrated into the instructional process. Vocabulary learning was also embedded within grammar-focused lessons rather than being explicitly structured as a lexical learning objective. These findings indicate that although multisensory techniques were used in the classroom, their implementation remained implicit and did not yet reflect a structured multisensory instructional framework. The study highlights the need for more deliberate multisensory instructional design to support vocabulary development among dyslexic learners in inclusive EFL classrooms.